The impact of traumatic brain injury on cognitive and neuropsychiatric symptoms of Parkinson's disease. (2nd January 2020) - Joyce, Julie M.; Monchi, Oury; Ismail, Zahinoor; Kibreab, Mekale; Cheetham, Jenelle; Kathol, Iris; Sarna, Justyna; Martino, Davide; Debert, Chantel T.
Abstract: The objective was to determine whether a history of traumatic brain injury (TBI) was associated with Parkinson's Disease (PD) and specific cognitive, motor, and neuropsychiatric symptoms. A cross-sectional cohort study of 120 participants aged 60–85 years old (48 females) were recruited (69 PD and 51 healthy controls). Assessments included demographic information, neuropsychological tests, a motor evaluation, neuropsychiatric questionnaires, and the Brain Injury Screening Questionnaire. A history of TBI or number of TBIs was not significantly related to an increased risk of developing PD or poorer motor scores on the United Parkinson Disease Rating Scale part 3. There was a significant negative correlation between number of TBI's and mean z -scores of global cognition ( rs (69) = −0.338, p = 0.004), executive function ( rs (69) = −0.251, p = 0.038), memory ( rs (69) = −0.262, p = 0.029), and language ( rs (69) = −0.245, p = 0.042), and a significant positive correlation on the Beck Depression Inventory II ( rs (69) = 0.285, p = 0.018) and the Patient Health Questionnaire–9 (PHQ-9) ( rs (69) = 0.326, p = 0.006) in the PD group only. In conclusion, a history of TBI was negatively associated with cognition and positively associated with depressive symptoms in patients with PD, but not with motor symptoms.